Mesoporous Hydroxyapatite/Chitosan Loaded With Recombinant-Human Amelogenin Could Enhance Antibacterial Effect and Promote Periodontal Regeneration - Liao, Yue; Li, Huxiao; Shu, Rong; Chen, Huiwen; Zhao, Liping; Song, Zhongchen; Zhou, Wei (Frontiers in Cellular and Infection Microbiology, 2020)
The recovery of impaired periodontium is still a challenge to the treatment of periodontitis. This study was the first to apply the mesoporous hydroxyapatites/chitosan (mHA/CS) composite scaffold to periodontal regeneration. This aim of our study is to evaluate the biological effects of mesoporous hydroxyapatite/chitosan (mHA/CS) loaded with recombinant human amelogenin (rhAm) on periodontal regeneration. The physicochemical properties of mHA/CS scaffolds were examined by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM) and Brunauer–Emmett–Teller (BET) analysis. Then, the biological effects of the mHA/CS loaded with rhAm were evaluated, including antibacterial effect, controlled-release capacity, osteogenic and cementogenic effects in vitro and in vivo. The analyses showed that the mHA/CS particles were 2 μm in diameter and had a uniform pore size. The mesoporous structure was 7 nm in diameter and its surface area was 33.95 m2/g. The scaffold exhibited antibacterial effects against Fusobacterium nucleatum and Porphyromonas gingivalis. The mHA/CS scaffold could sustainably release rhAm. The mHA/CS loaded with 20 μg/ml rhAm upregulated ALP activity, the expression levels of osteogenesis-related genes and proteins in vitro. Additionally, it could promote the formation of cementum-like tissue in vivo. Our findings suggest that mHA/CS loaded with 20 μg/ml rhAm could inhibit the growth of periodontal pathogens and promote the formation of bone and cementum-like tissue.